Introducing System Center Configuration Manager - Hampson, Gerry; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"System Center Configuration Manager (ConfigMgr) is the flagship systems management product from Microsoft that provides a comprehensive management solution for computer systems. It provides patch management, OS deployment, remote control, endpoint protection, and many other services. This is the first of two courses in the series, providing beginner-level tutorial videos on ConfigMgr. They will get you started with this powerful solution and eventually enable you to effectively manage your resources. We'll teach you how to install and configure ConfigMgr, manage your devices, deploy operating systems in the enterprise, deploy and manage applications. You'll discover how to perform patch management, adhere to compliance, protect your infrastructure, and much more. By the end of this series, you will be able to provide effective IT services to your organization by enabling secure software deployment, quickly applying software patches and updates, rebuilding a system that has been compromised, and keeping your systems compliant. In this course we start with an introduction to ConfigMgr and show you how to design, install and upgrade the product. Then we discuss preliminary configuration of the solution, including discovery and boundaries, client installation, collections, compliance, hardware and software inventory, role-based administration, backup, recovery and site maintenance."--Resource description page.
Presenter, Gerry Hampson.
Title from title screen (viewed May 15, 2017).
Date of publication from resource description page.
Keywords: Microsoft System center; Computer networks -- Management; Client/server computing; Electronic books